Antimicrobial activity of antidepressants on normal gut microbiota: Results of the in vitro study - Rukavishnikov, Grigory; Leonova, Lubov; Kasyanov, Evgeny; Leonov, Vadim; Neznanov, Nikholay; Mazo, Galina (Frontiers in Behavioral Neuroscience, 2023)
There is limited data on the antidepressants effects on normal gut microbiota and the consequences on treatment outcomes. The aim of the study: was to evaluate the growth kinetics of normal human gut microorganisms with antidepressants most common in routine clinical practice. Materials and methods: Research objects were species of microorganisms representing normal gut microbiota: Staphylococcus aureus АТСС 25923, Escherichia coli АТСС 25922, Candida albicans АТСС 24433, Bifidobacterium 791, Enterococcus faecalis ATCC 29212, Lactobacillus rhamnosus ATCC 53103. All microorganisms were cultivated in Schaedler broth (HiMedia) under aerobic / anaerobic conditions. The active substances of all studied antidepressants (fluvoxamine, fluoxetine, escitalopram, duloxetine, venlafaxine, mirtazapine) were extracted from grinded preparations by dimethyl sulfoxide and centrifuged. Each solution of antidepressants was added to a Schaedler broth containing a certain microorganism’s strain and diluted to final concentrations - 200 μg/ml, 500 μg/ml, 700 μg/ml. For a quantitative assessment of the effect the specific growth rates (μ, h-1) of microorganisms were calculated as the slope of the initial part of the growth curve in coordinates (lnA, t). To evaluate the antidepressant effects on representatives of the normal microbiota in vitro, the following parameters were chosen: specific growth rate and IC50. Results: All antidepressants had an inhibitory effect on the growth of all studied microorganisms. Fluvoxamine and venlafaxine had the least effect on the growth activity of all studied microorganisms. Fluoxetine showed a pronounced effect on growth activity against E. coli, E. feacalis, S. aureus, and the least effect against C. albicans. Escitalopram had a greater effect on the growth rate of E. coli, E. feacalis, B. bifidum, L. rhamnosus and C. albicans, which puts it among the leaders in terms of its effect on the growth activity of the microorganisms we studied. Mirtazapine, according to the results of our experiment, showed the greatest activity against L. rhamnosus and C. albicans. Conclusions: Our results confirm the effects of antidepressants on the growth activity of the normal gut microbiota individual strains. Further study of the antimicrobial activity of antidepressants may become one of the new directions for optimizing the personalized therapy of patients with depression.